Upaya Peningkatan Hasil Belajar Matematika Menggunakan Model Pembelajaran Langsung (Direct Instruction) Bagi Siswa Kelas V Sekolah Dasar - Dina Carlina; Fauzi Fadliansyah (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
This research was used to determine the improvement in Mathematics learning outcomes through the direct instruction model at SDN 02 Astra Ksetra. The problem faced was that the learning outcomes obtained were still low, so using this learning model gave students the opportunity to observe specifically, remember and imitate. what the teacher models or exemplifies. The results of learning improvement I, the average student test score, were found to show an increase in learning outcomes in improvement II, with the average also increasing. The results of improvement I obtained an overall learning completion percentage of 51.85% and experienced an increase in improvement (Cycle) II of 74.07%. So overall learning is said to be successful.